Human ileal bile acid transporter gene ASBT (SLC10A2) is transactivated by the glucocorticoid receptor. Issue 1 (18th December 2003) - Jung, D; Fantin, A C; Scheurer, U; Fried, M; Kullak-Ublick, G A
Abstract : Background: Patients with Crohn's disease suffer from intestinal bile acid malabsorption. Intestinal bile acid absorption is mediated by the apical sodium dependent bile acid transporter ASBT/IBAT ( SLC10A2 ). In rats, ASBT is induced by glucocorticoids. Aims: To study whether human ASBT is activated by glucocorticoids and to elucidate the mechanism of regulation. Patients and methods: ASBT expression in ileal biopsies from patients with Crohn's disease and from healthy subjects was quantified by western blot. ASBT promoter function was studied in luciferase assays and by electrophoretic mobility shift assay. Results: In 16 patients with Crohn's disease, ASBT expression was reduced to 69 (7.5)% compared with healthy controls (mean (SEM); p = 0.01). In 10 healthy male volunteers, ASBT protein expression was increased 1.34 (0.11)-fold (mean (SEM); p<0.05) after 21 days' intake of budesonide (9 mg/day) whereas expression of the peptide transporter 1 was unaffected. Reporter constructs of the human ASBT promoter were activated 15–20-fold by coexpression of the glucocorticoid receptor (GR) and exposure to the GR ligands dexamethasone or budesonide. Two glucocorticoid response elements in the ASBT promoter, arranged as inverted hexanucleotide repeats (IR3 elements), conferred inducibility by GR and dexamethasone in a heterologous promoter context and were shown to bind GR in mobility shift assays. Conclusions: Human ASBT is induced by glucocorticoids in vitro and in vivo. Induction of ASBT by glucocorticoids could be beneficial in patients with Crohn's disease who exhibit reduced ASBT expression. This study identifies ASBT as a novel target of glucocorticoid controlled gene regulation in the human intestine.